Development of DIMIBA Web-Based Learning Media Using Chunking to Support Fourth-Grade Reading Comprehension at SDN 05 Sibawek - Seriati Seriati; Masriani Masriani; Siti Halidjah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to develop a web-based interactive learning media called DIMIBA (Diri Mali Ia Bajual) to support fourth-grade elementary school students’ reading comprehension, particularly in identifying the main idea. The study was motivated by students’ low reading comprehension skills, which are associated with conventional teaching methods that present texts in long and less structured forms. To address this issue, the media integrates a chunking strategy, which organizes information into smaller, meaningful units to facilitate understanding and reduce cognitive load. This research employed the Research and Development (R&D) method using the ADDIE model, which was limited to the analysis, design, and development stages. Data were collected through observations, interviews, questionnaires, and expert validation. The developed media was evaluated by material, media, and language experts and further assessed through teacher and student responses. The results showed that the DIMIBA learning media achieved an average validation score of 88%, categorized as very good. Student responses reached 97%, while teacher responses reached 93.74%, both falling within the very good category. These findings indicate that the integration of the chunking strategy in web-based learning media can support reading comprehension and increase student engagement. Therefore, DIMIBA is considered a feasible alternative learning medium for elementary schools. Further studies are recommended to examine its effectiveness in improving students’ learning outcomes.